Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1053/euhj.2001.2774
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognosis of electrocardiographic left ventricular hypertrophy, ST segment depression and negative T-wave. The Copenhagen City Heart Study

Abstract: Electrocardiographic left ventricular hypertrophy with ST depression and negative T wave changes are the electrocardiographic abnormalities with the greatest prognostic information for future cardiac events. Electrocardiographic negative T waves, ST depression and negative T wave abnormalities and left ventricular hypertrophy with negative T waves, also have prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 30 publications
7
81
0
4
Order By: Relevance
“…It may also reflect differences in MI endpoint definition applied in the [14]. However, this is a relatively low-prevalence condition (5-10%) [41], and not having these data available would lead to our estimates being slight underestimates. Studies indicate that use of lipid-lowering agents in HIVinfected patients is associated with moderate effects on lipid levels [42,43].…”
Section: Discussionmentioning
confidence: 70%
“…It may also reflect differences in MI endpoint definition applied in the [14]. However, this is a relatively low-prevalence condition (5-10%) [41], and not having these data available would lead to our estimates being slight underestimates. Studies indicate that use of lipid-lowering agents in HIVinfected patients is associated with moderate effects on lipid levels [42,43].…”
Section: Discussionmentioning
confidence: 70%
“…In the Copenhagen City Heart Study (a population-based study), men younger than 55 years of age with voltage-only LVH (employing the Minnesota code) had the same risk of developing future coronary artery disease and myocardial infarction as those with a normal ECG. 13 This 20 In addition, the Framingham investigators found that the excess CV risk associated with voltage-only LVH was eliminated when adjusted for hypertension. 21 They postulated that the voltageonly LVH in hypertensive individuals reflects chiefly the severity and duration of the associated hypertension and therefore signifies ventricular muscle hypertrophy without myocardial damage.…”
Section: Voltage Ecg Lvh Criteria As a Prognostic Indicatormentioning
confidence: 99%
“…Although a number of previous studies have demonstrated the predictive value of ECG LV hypertrophy criteria which include some measure of the qualitative ECG strain pattern in their determination for the development of heart failure (8-12), these studies did not examine the predictive value of strain alone. In addition, among studies that examined ECG strain alone for Cardiovascular outcomes (7,(13)(14)(15)(16)(17)(18), the relationship of ECG strain to developing heart failure was evaluated in only one (7). In a previous report on hypertensive patients with ECG LV hypertrophy in the LIFE study (7), typical strain on the baseline ECG was a significant predictor of new-onset heart failure and heart failure mortality.…”
mentioning
confidence: 99%
“…First, it is unclear to what degree these findings in American Indians can be extrapolated to other ethnic populations. However, the demonstrated predictive value of ECG strain and minor degrees of STD for Cardiovascular morbidity and mortality in other populations (7,8,(14)(15)(16)(17)(18)(19) quantitative analysis of lateral STD will stratify the risk of developing heart failure in other populations as well. Second, the absence of information from serial ECGs precludes analysis of the impact of changes in STD on risk.…”
mentioning
confidence: 99%